2015
DOI: 10.2174/1381612821666150316115412
|View full text |Cite
|
Sign up to set email alerts
|

History and Milestones of Mouse Models of Autoimmune Diseases

Abstract: Autoimmune diseases are a group of disorders mediated by self-reactive T cells and/or autoantibodies. Mice, as the most widely used animal for modeling autoimmune disorders, have been extensively used in the investigation of disease pathogenesis as well as in the search for novel therapeutics. Since the first mouse model of multiple sclerosis was established more than 60 years ago, hundreds of mouse models have been established for tens of autoimmune diseases. These mouse models can be divided into three categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Due to the immune tolerance, induction of some autoantibodies requires immunization with modified antoantigens, e.g. recombinant autoantigens bearing a GST-tag, coupling of autoantigens to OVA, or heterologous autoantigens [ 27 , 28 ]. With these modifications, non-self T cell epitopes are introduced and help B cells to produce autoantibodies via linked recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the immune tolerance, induction of some autoantibodies requires immunization with modified antoantigens, e.g. recombinant autoantigens bearing a GST-tag, coupling of autoantigens to OVA, or heterologous autoantigens [ 27 , 28 ]. With these modifications, non-self T cell epitopes are introduced and help B cells to produce autoantibodies via linked recognition.…”
Section: Discussionmentioning
confidence: 99%
“…In the first phase (0-8 weeks of age), several aberrant genetic, physiological, and biochemical activities occur prior to the initiation of disease. The second phase (8)(9)(10)(11)(12)(13)(14)(15)(16) weeks of age) is characterized by inflammatory cell infiltration in exocrine glands and the production of autoantibodies and proinflammatory cytokines. Finally, in the third phase (>16 weeks of age), the function of the salivary and lacrimal glands (LG) is impaired due to autoimmune-mediated attack (18,19,57).…”
Section: Genetic Modelsmentioning
confidence: 99%
“…Similar to induced models of many other autoimmune diseases (14), the first induced model of SS was established by immunizing animals with tissue/cell extracts. In 1974, White et al reported an experimental rat model of sialadenitis induced by immunization with allogeneic submandibular gland homogenate emulsified in Freund's complete adjuvant (FCA) (111).…”
Section: Salivary Gland Protein-induced Mouse Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…These facts alone call for clinically relevant AA research models, in which the as yet insufficiently understood pathobiology of AA can be systematically and mechanistically dissected and in which new AA treatment and prevention strategies can be explored in vivo at the preclinical level, ideally with good predictive value for the outcomes that can realistically be expected in patients with AA. Mouse models have provided invaluable research tools for dissecting the roles of extrinsic and intrinsic factors and various underlying immune pathologies in various autoimmune skin diseases (Yu et al, 2015, Yu andPetersen, 2018). Lessons that have been learned from mouse models for psoriasis (Jin et al, 2018;Mykicki et al, 2017;Nakajima and Sano, 2018), atopic dermatitis (Lin et al, 2018;Nakajima et al, 2019;Yamada et al, 2018), and vitiligo (Riding et al, 2019) have greatly advanced our understanding of disease pathogenesis and for exploring novel therapeutic strategies at the preclinical level.…”
Section: Introductionmentioning
confidence: 99%